2016
DOI: 10.1371/journal.pone.0167683
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clinical Decision Support Systems on Medication Safety: An Overview

Abstract: BackgroundThe clinical decision support system(CDSS) has potential to improving medication safety. However, the effects of the intervention were conflicting and uncertain. Meanwhile, the reporting and methodological quality of this field were unknown.ObjectiveThe aim of this overview is to evaluate the effects of CDSS on medication safety and to examine the methodological and reporting quality.MethodsPubMed, Embase and Cochrane Library were searched to August 2015. Systematic reviews (SRs) investigating the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 47 publications
2
87
0
1
Order By: Relevance
“…As regards our second research question, namely to understand the advantages and disadvantages of CDSS use, we found that current CDSSs could potentially improve services within the healthcare system, time to decision, and health-related quality of life for patients; and reduce both healthcare costs and medical error rates [8,12]. However, as with any healthcare innovation, CDSSs should be rigorously assessed before dissemination into clinical practice, i.e., corroborate that indeed it improves clinical care or patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards our second research question, namely to understand the advantages and disadvantages of CDSS use, we found that current CDSSs could potentially improve services within the healthcare system, time to decision, and health-related quality of life for patients; and reduce both healthcare costs and medical error rates [8,12]. However, as with any healthcare innovation, CDSSs should be rigorously assessed before dissemination into clinical practice, i.e., corroborate that indeed it improves clinical care or patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A CDSS has two principal action areas: (i) clinical decision-making and (ii) medical education [7]. Currently, CDSSs are used in many medical areas to improve healthcare system services [8], decision timing [8], and health-related quality of life for patients [8]; such systems can reduce both healthcare costs [8-10] and medical error rates [11][12][13]. CDSSs have potential benefits and drawbacks in implementation and use in clinical practice, specifically in oncology [14].…”
mentioning
confidence: 99%
“…Outside the scope of oncology, several reviews reported positive effects of CDSSs on process outcomes. The review of Jia et al assessed the effects of CDSSs on medication prescription, medication dose and other drug related outcomes [37]. This study reported that CDSSs significantly impact medication administration in 108 out 143 studies included [37].…”
Section: Agreements and Disagreements With Literaturementioning
confidence: 99%
“…The review of Jia et al assessed the effects of CDSSs on medication prescription, medication dose and other drug related outcomes [37]. This study reported that CDSSs significantly impact medication administration in 108 out 143 studies included [37]. The review of Bright et al assessed CDSSs with a broad scope in healthcare [38].…”
Section: Agreements and Disagreements With Literaturementioning
confidence: 99%
“…Although periodic medication review can lead to prevention of PIP [15,16], there is no consensus on what such a review should comprise. In recent years, it has become apparent that Clinical Decision Support Systems (CDSSs) can provide support in medication reviews and could possibly reduce medication-related errors [17][18][19]. CDSSs could therefore contribute in improving quality of care and outcomes in older patients.…”
Section: Introductionmentioning
confidence: 99%